2020
DOI: 10.1101/2020.07.24.218776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-dimensional video-based analysis of human gait using pose estimation

Abstract: Walking is the primary mode of human locomotion. Accordingly, people have been interested in studying human gait since at least the fourth century BC. Human gait analysis is now common in many fields of clinical and basic research, but gold standard approaches – e.g., three-dimensional motion capture, instrumented mats or footwear, and wearables – are often expensive, immobile, data-limited, and/or require specialized equipment or expertise for operation. Recent advances in video-based pose estimation have sug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…The pros and cons of using currently available pose estimation algorithms for measurement of human movement have been discussed at length (29), and we will discuss our own impressions and suggestions below. Despite current limitations, this study and our prior work (21) have shown promising results when comparing pose estimation outputs to groundtruth measurements of clinically relevant movement parameters. We anticipate that the accuracy of human pose estimation algorithms will continue to improve, and we offer that this emerging technology has significant potential for versatile, quantitative, remote assessment of human motor function.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The pros and cons of using currently available pose estimation algorithms for measurement of human movement have been discussed at length (29), and we will discuss our own impressions and suggestions below. Despite current limitations, this study and our prior work (21) have shown promising results when comparing pose estimation outputs to groundtruth measurements of clinically relevant movement parameters. We anticipate that the accuracy of human pose estimation algorithms will continue to improve, and we offer that this emerging technology has significant potential for versatile, quantitative, remote assessment of human motor function.…”
Section: Discussionmentioning
confidence: 85%
“…While emerging evidence suggests significant potential for tracking repetitive movements using video-based pose estimation approaches, here we addressed two important unmet needs: 1) testing across a range of clinically relevant tasks spanning the upper and lower extremities, and 2) assessment of accuracy via validation against ground-truth measurement. Based on our prior work (21), we expected good agreement between the OpenPose estimates of movement frequency and ground-truth measurement. We also share our perspectives regarding limitations, potential problems, and suggestions for successful analysis.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…OpenPose has already been used in gait analysis research. 34,44,45 We believe that our work here adds to the research on using accessible and affordable deep-learning-based keypoint estimators in the analysis of complex movements such as dance.…”
Section: Discussionmentioning
confidence: 92%
“…Erika D’Antonio (2020) [ 34 ] used OpenPose to investigate the accuracy of such a system estimating kinematic parameters of human gait using two webcams synchronized with inconclusive results, commenting on the need for further analysis. Stenum (2020) [ 35 ] used a system based on RGB images recording a person from the side while walking to obtain gait parameters employing OpenPose, with high accuracy of 0.89 for ankle angle.…”
Section: Related Workmentioning
confidence: 99%